Changes in muscle composition and energy contents of golden mahseer, Torputitora (Hamilton) in relation to its spawning cycle - Basade, Yasmeen; Kapila, Suman; Kapila, Rajeev (Indian Journal of Fisheries, 2011)
Seasonal changes in the muscle compositions and energy contents of male and female fishes of golden mahseer, Tor putitora (Hamilton) were examined with regard to their spawning cycle during the year 1996. In pre-spawning season (April to May), protein, fat, glycogen and energy contents tended to increase as a percentage of muscle composition, whereas, during spawning season (June to September) the same decreased and reached a minimum in post-spawning season (October to November), indicating significant (p<0.01) muscle energy reserves utilization for spawning. Protein, fat, and glycogen contents were inversely proportional to the moisture content and directly to each other Ash varied modestly regardless of the spawning state in males but in females increased significantly (p<0.01) from pre-spawning season through spawning season to post-spawning season accounting positive correlation (r=0.90, p<0.01) with moisture contents.